Diagenesis does not invent anything new: Precise replication of conodont structures by secondary apatite - Annalisa Ferretti (Nature Portfolio, 2017)
Abstract Conodont elements are important archives of sea/pore water chemistry yet they often exhibit evidence of diagenetic mineral overgrowth which may be biasing measurents. We decided to investigate this phenomenon by characterising chemically and crystallographically, the original biomineral tissue and the diagenetic mineral nature of conodont elements from the Ordovician of Normandy. Diagenetic apatite crystals observed on the surface of conodont elements show distinctive large columnar, blocky or web-like microtextures. We demonstrate that these apatite neo-crystals exhibit the same chemical composition as the original fossil structure. X-ray microdiffraction has been applied herein for the first time to conodont structural investigation. Analyses of the entire conodont element surface of a variety of species have revealed the existence of a clear pattern of crystal preferred orientation. No significant difference in unit cell parameters was documented between the newly formed apatite crystals and those of the smooth conodont surfaces, thus it emerges from our research that diagenesis has strictly replicated the unit cell signature of the older crystals.